Between the street and Aso Rock*: the role of Nigerian trade unions in popular protests. Issue 1 (2nd January 2018) - Houeland, Camilla
ABSTRACT: The trade unions' instrumental role in four decades of successful popular resistance against subsidy removals is widely recognised, but insufficiently understood due to inadequate consideration of the particularities of labour. The subsidy contestations are considered a barometer of Nigerian politics, and the 2012 subsidy protests – often referred as Occupy Nigeria – was one of the largest popular mobilisations in Nigerian history. Whereas unionists described the outcome as a successful demonstration of popular sovereignty, other protesters blamed the unions for unfulfilled democratic opportunities and for succumbing to bribery. With labour theoretical perspectives, this article critically examines the trade unions' positions, actions and relations during those protests. The article demonstrates, in practice, not only how the unions' capacities to mobilise, strike and negotiate, were instrumental to the reinstatement of the subsidy, but also how trade unions' agency is both enabled and constrained by labour's multiple embeddedness in state, civil society and the market.